ENHANCED RECOVERY PROTOCOLS IN CARDIAC SURGERY: A PROSPECTIVE STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Cardiac surgery is associated with considerable postoperative morbidity, prolonged intensive care unit (ICU) stay, and delayed functional recovery. Conventional perioperative practices such as prolonged fasting, delayed mobilization, and limited pain control contribute to suboptimal outcomes. Enhanced Recovery After Surgery (ERAS) protocols are evidence-based, multidisciplinary strategies designed to reduce surgical stress, optimize perioperative care, and accelerate recovery. Objectives: This study aimed to evaluate the effectiveness of ERAS protocols in reducing ICU stay, hospital stay, postoperative complications, and improving overall recovery in patients undergoing cardiac surgery. Methods: A prospective observational study was conducted at a tertiary care center from April 2025 to March 2026, including 100 patients undergoing elective cardiac surgery. ERAS protocols implemented in this study included preoperative counselling, reduced fasting duration, optimized nutritional support, multimodal analgesia, early extubation, early initiation of oral intake, and early mobilization. Clinical outcomes assessed were ICU stay, hospital stay, time to mobilization, postoperative complications, and readmission rates. Data were analyzed using descriptive statistics, with continuous variables expressed as mean ± standard deviation and categorical variables as percentages. A p-value < 0.05 was considered statistically significant. Results: The implementation of ERAS protocols resulted in favorable clinical outcomes. The mean ICU stay was 2.1 ± 0.8 days, and the mean hospital stay was 6.5 ± 1.5 days, indicating faster postoperative recovery. Early mobilization within 24 hours was achieved in 82% of patients, while oral intake was initiated within 12 ± 4 hours. Postoperative complications were relatively low, including arrhythmias in 12% of patients, pulmonary complications in 10%, and surgical site infections in 6%. The readmission rate was 5%. Statistical analysis demonstrated significant reductions in ICU and hospital stay compared to conventional care benchmarks. Conclusion: ERAS protocols significantly enhance postoperative recovery in cardiac surgery patients by reducing ICU stay, hospital stay, and complication rates. These findings support the routine adoption of ERAS pathways in cardiac surgical practice to improve patient outcomes and optimize healthcare resource utilization.